Moderated digital social therapy for young people with emerging mental health problems: A user-centered mixed-method design and usability study - van Doorn, Marilon; Monsanto, Anne; Boeschoten, Cato M.; van Amelsvoort, Thérèse; Popma, Arne; Öry, Ferko G.; Alvarez-Jimenez, Mario; Gleeson, John; Jaspers, Monique W. M.; Nieman, Dorien H. (Frontiers in Digital Health, 2023)
Introduction Over 25% of Dutch young people are psychologically unhealthy. Individual and societal consequences that follow from having mental health complaints at this age are substantial. Young people need care which is often unavailable. ENgage YOung people earlY (ENYOY) is a moderated digital social therapy-platform that aims to help youngsters with emerging mental health complaints. Comprehensive research is being conducted into the effects and to optimize and implement the ENYOY-platform throughout the Netherlands. The aim of this study is to explore the usability and user experience of the ENYOY-platform. Methods A user-centered mixed-method design was chosen. 26 young people aged 16–25 with emerging mental health complaints participated. Semi-structured interviews were conducted to explore usability, user-friendliness, impact, accessibility, inclusivity, and connection (Phase 1). Phase 2 assessed usability problems using the concurrent and retrospective Think Aloud-method. User experience and perceived helpfulness were assessed using a 10-point rating scale and semi-structured interviews (Phase 3). The Health Information Technology Usability Evaluation Scale (Health-ITUES; Phase 1) and System Usability Scale (SUS; Phase 2 and 3) were administered. Qualitative data was analyzed using thematic analysis. Task completion rate and time were tracked and usability problems were categorized using the Nielsen's rating scale (Phase 2). Results Adequate to high usability was found (Phase 1 Health-ITUES 4.0(0.34); Phase 2 SUS 69,5(13,70); Phase 3 SUS 71,6(5,63)). Findings from Phase 1 (N = 10) indicated that users viewed ENYOY as a user-friendly, safe, accessible, and inclusive initiative which helped them reduce their mental health complaints and improve quality of life. Phase 2 (N = 10) uncovered 18 usability problems of which 5 of major severity (e.g. troubles accessing the platform). Findings from Phase 3 (N = 6) suggested that users perceived the coaching calls the most helpful [9(0.71)] followed by the therapy content [6.25(1.41)]. Users liked the social networking aspect but rated it least helpful [6(2.1)] due to inactivity. Conclusion The ENYOY-platform has been found to have adequate to high usability and positive user experiences were reported. All findings will be transferred to the developmental team to improve the platform. Other evaluation methods and paring these with quantitative outcomes could provide additional insight in future research.